(untitled) (Indian Journal of Animal Production and Management, 2024)
A field study was done to know the existing breeding, feeding and management practices adopted by the milk producers in delta, upland and agency areas of East Godavari district of Andhra Pradesh. The practice of rearing of high milk yielding dairy animals was higher in Godavari delta (85%) followed by upland (63%) and agency area (13%). The practice of green fodder production was higher in Godavari delta (78%) and upland area (61%) than that in agency area (13%). Majority of milk producers in upland (95%), Godavari delta (87%) and agency area (77%) provided drinking water to milk animals from tube well. Thatched roofing was practiced by majority of milk producers in agency (98%) area. Majority of milk producers in Godavari delta (90%) and upland area (56%) marketed the milk to the cooperative and private dairies, whereas, agency milk producers (65%) marketed milk to milk vendors.